A poetic and dystopian quadrilateral: Mayakovsky and Frank O'Hara, Essenin and Jim Harrison (Colloquia Comparativa Litterarum, 2025)
The Soviet Union, the perfect example of a dystopia, presented itself as a paradise for the proletariat. The United States, on the other hand, was, at the same time, a land of technical progress and capitalist hell from the Communist point of view. Separated by the Atlantic Ocean, these two best enemies dreamed of and confronted each other. But this is above all a tragic quadrilateral where Mayakovsky and O'Hara, Essenin and Harrison meet. For their poetic utopia will collide with dystopian reality.
Keywords: poetry; American; Soviet; Mayakovsky; O'Hara; Essenin; Harrison